PENGARUH CITRA DESTINASI, DAYA TARIK WISATA DAN AKSESIBILITAS TERHADAP KEPUASAN PENGUNJUNG OBYEK WISATA PIJAR PARK KUDUS - Adinda Dwi Hanifa; Nurul Komaryatin (JURNAL ILMIAH EDUNOMIKA, 2024)
There are several factors that become the reason for tourists to visit a tourist destination, including destination image, attractiveness and accessibility. The purpose of this study was to determine the effect of destination image, tourist attraction and accessibility on visitor satisfaction at Pijar Park Kudus tourist attraction. This type of research uses a quantitative approach. The population of this study were all visitors who had come to Pijar Park Kudus Tourism. The sampling method uses nonprobability sampling with purposive sampling technique used as a strategy in selecting respondents. Sample measurement using the slovin formula where a sample of 98.5 people was obtained and rounded up to 100 people. The data analysis used in this research is validity test, reliability test, classical assumption test, and hypothesis testing using SPSS version 25. The results showed that destination image has a positive effect on visitor satisfaction at Pijar Park tourist attraction, attractiveness has a positive effect on visitor satisfaction at Pijar Park tourist attraction and accessibility has a positive effect on visitor satisfaction at Pijar Park Kudus Tourism Object. Destination image has the highest influence, so it can be said that destination image is the most dominant variable in influencing visitor satisfaction. Keywords : destination image, tourist attraction, accessibility and visitor satisfaction